Prevalence of Burnout, Secondary Traumatic Stress, Anxiety, and Depression Among Maternal and Neonatal Healthcare Staff in Two Tertiary Hospitals in Zambia - Hope, Namonje; Christine, Jere; Jolyon, Poole (International Journal of Global Health, 2025)
Background Healthcare worker stress, anxiety, burnout, and trauma have been widely documented across global healthcare systems. Staff in maternal and neonatal units frequently encounter emotionally distressing events and work under high pressure with limited resources. In Zambia, despite some gains in reducing maternal and neonatal mortality, fatality rates remain above national targets, exposing staff to repeated occupational trauma. Objective(s) This study aimed to assess the psychological well-being of staff in maternal and neonatal intensive care units, identify specific needs and stressors, and develop practical recommendations to improve resilience and support staff mental health. Methods A mixed-methods cross-sectional study was conducted at Ndola Teaching Hospital (NTH) and Arthur Davison Children's Hospital (ADCH), two major tertiary hospitals in Zambia. Data were collected over four days in February 2025. The study included 87 (out of 161) healthcare professionals, including nurses, midwives, and doctors. The Goldberg Anxiety and Depression Scale (GADS) and the Professional Quality of Life Scale Version 5 (ProQOL 5) were used to collect quantitative data, which were analysed using descriptive statistics and 95% confidence intervals (CI). Open-ended survey questions provided qualitative data, which were analysed using thematic analysis. Ethical approval was granted by the hospital ethics committee. Results High rates of clinical symptoms were observed. The overall prevalence of symptoms in the past 30 days was: anxiety (62%), depression (68%), burnout (50%), and secondary traumatic stress (46%). Junior doctors demonstrated the highest rates of depression (83%) and burnout (67%). The obstetrics and gynaecology and labour wards had the highest rates of secondary traumatic stress symptoms. Key qualitative themes identified were professional stressors, team and leadership issues, and the emotional burden of the work. Conclusion This study highlights an urgent need for both psychological and organizational support for maternal and neonatal healthcare staff in Zambia. The findings indicate that burnout and secondary traumatic stress are highly prevalent, particularly among junior doctors and those in high-risk wards. Targeted interventions at both systemic and individual levels are necessary to protect the well-being of healthcare workers and improve patient outcomes.
Keywords: Burnout; Secondary Traumatic Stress; Maternal Health; Neonatal Care; Zambia; Healthcare Workers